The Institutional Roots of M&A Success: Evidence from European Business Environments - Irina Chiriac; Valentina Diana Rusu (Administrative Sciences, 2025)
This study investigates the relationship between the business environment and the financial performance of companies engaged in mergers and acquisitions (M&As), with a particular emphasis on how “ease of doing business” (EDB) indicators affect post-merger outcomes, as measured by return on assets (ROA), return on equity (ROE), and profit margin (PM). We consider a sample of 230 firms from fifteen European countries (Bulgaria, Cyprus, Denmark, France, Greece, Hungary, Italy, Germany, Lithuania, The Netherlands, Norway, Poland, Romania, Slovakia, and Spain) grouped according to COFACE criteria for five years (2015–2019). By applying panel data methods, the research highlights that, three years after the merger in low-risk countries, there is an increase in return on equity, better asset recovery, and economies of scale, largely due to effective government policies. The study highlights the differentiated effects of specific EDB sub-indicators, providing insight into how tailored regulatory frameworks can enhance M&A success across varying economic contexts. The business environment can stimulate the performance of firms after mergers and acquisitions if the regulations are friendly to the firms and are adapted to the state of the country’s economy.